Digital Da'wah for Worship: Ghofar Zaen’s Adhan, Bilal, and Tilawah Tutorials on YouTube - Hasanah, Qoriah; Jannah, Siti Raudhatul; Wazis, Kun (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to investigate Ghofar Zaen's da'wah messages on YouTube through the delivery of material on tutorials on the adhan, bilal, and shalawat. This study was conducted from January to June 2023. This research used a qualitative study with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted using the interactive analysis model by Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that the tutorial content on adhan, bilal, and shalawat is presented to provide understanding to the public, particularly in the field of worship. The increasing interest of the public in online religious education has made Ghofar Zaen's worship channel videos popular among the audience. It is able to accommodate the community's need for information about worship, which is then produced into content. Its worship content has the potential to become a reference for religious knowledge among the community. The appeal of worship content has encouraged community involvement in accessing and learning online. This research is expected to strengthen online religious literacy, which has the potential to become an alternative source of reading for the community.